Վայոց ձորի մարզի նորակառոյց եկեղեցիները (2000—2021) - Մալոյեան, Արման (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В истории средневекового армянского церковного зодчества архитектурная школа Сюника занимает поистине почетное место с ее талантливыми зодчими, мастерами-строителями и мастерами хачкаров. Представители этой архитектурной школы оставили бессмертную память в монастыре средневекового армянского церковного зодчества и подняли армянское церковное зодчество на новый уровень. В 1991 году, позже в новой независимой Республике Армения, армянская церковная архитектура пережила возрождение и новый период роста. Современные армянские архитекторы и мастера-строители продолжают лучшие традиции средневековой армянской церковной архитектуры, применяя новые технологии, решения и идеи при строительстве новых церквей, в том числе церквей Вайоцдзорского региона. В этой статье мы представляем новопостроенные церкви и часовни Вайоцдзорской области Армении (церковь Св. Тиридата в Вайке, церковь Св. Анны в Малишке, церковь Св. Мариам в Агавнадзоре, церковь Св. Мариам Аствацацин в Мартиросе, церковь Св. Гаяне в Джермуке, часовня Св. Гаяне в Кечуте, часовня Св. Егише в Гндевазе, церковь Св. Саргиса в Елпине, церковь Св. Мариам Аствацацин в Ринде). В статье представлены архитектурные формы вышеназванных церквей и часовен, история строительства и другие сопутствующие вопросы. In the history of the medieval Armenian Church architecture, the architectural school of Syunik has a truly honorable place with its talented architects, master builders and cross-stone (khachkar) masters. Representatives of this architectural school left an indelible mark on the medieval Armenian church architecture and raised it to a new level. In 1991, later in the newly independent Republic of Armenia, the Armenian church architecture experienced a revival and a new period of growth. Contemporary Armenian architects and master builders continue the best traditions of the medieval Armenian church architecture, applying new technologies, solutions, and ideas in the construction of new churches, including those in the Vayots Dzor region. In this article, we present the newly built churches and chapels of the Vayots Dzor region of Armenia (St. Tiridates Church in Vayk, St. Anna Church in Malishka, St. Mariam Church in Aghavnadzor, St. Mariam Astvatsatsin Church in Martiros, St. Yeghishe Chapel in Gndevaz, St. Sarkis Church in Yelpin, St. Gayane Chapel in Kechut, St. Gayane Church in Jermuk, St. Mariam Astvatsatsin Church in Rind). In the article, we present the architectural forms of the above-mentioned churches and chapels, the history of construction and other related issues.
Keywords: Հայ Եկեղեցի; Վայոց Ձոր